Inclusive Teaching: Strategies for Promoting Equity in the College Classroom - Leslie M. Boon (University of Windsor, 2023)
This article is a book review of Inclusive Teaching: Strategies for Promoting Equity in the College Classroom by Kelly A. Hogan and Viji Sathay.